Evaluation of vitamin D status and its association with dietary patterns and sociodemographic factors among adolescents attending the outpatient department of selected hospitals in Dhaka city, Bangladesh (Bioresearch Communications, 2024)
Objectives: The current study aims to evaluate the vitamin D status of adolescents undergoing treatment at selected tertiary hospitals’ outpatient departments (OPD) in Dhaka city and to look at the relationships between vitamin D levels and sociodemographic characteristics and dietary habits. Methods: The study followed a cross-sectional study design targeting adolescents (10–19 years old) who came to the OPD of selected tertiary hospitals. Following the convenience sampling procedure, a total of 384 adolescents were included in the study whose medical records were available with vitamin D status. Vitamin D status was evaluated based on medical reports. In addition, dietary habits were recorded using the Food Frequency Questionnaire (FFQ). To ascertain the factors influencing the individual’s vitamin D status, a multinomial logistic regression model was constructed. Results: Approximately two-thirds of the respondents were female, and over 58% of the respondents were young adolescents (ages 10 to 14). It was discovered that 32% of the adolescents lacked enough vitamin D, while 36.7% of them had insufficient levels of this nutrient. The deficiency level was considerably higher in older adolescents (15–19 years old). Girls were inadequate by 36.2% as opposed to boys, who were lacking by 24.6%. Deficits in vitamin D were more prevalent in women with low-paying employment, mothers with primary/below or no institutional education, mothers from lower-income families, etc., in addition to other sociodemographic characteristics. In terms of eating patterns, the study suggested that participants who frequently ate foods strong in vitamin D, like dairy, meat, eggs, nuts, fatty fish, fruits, and vegetables, as well as Horlicks, showed a decreased incidence of vitamin D deficiency. The mother's occupation (service holder), the less frequent use of dairy, meat, fortified oil, and Horlicks were discovered to be highly predictive factors of vitamin D deficiency, according to a multinomial logistic regression study. Conclusion: According to the current study, eating foods high in vitamin D, such as dairy, beef, fortified oil, and Horlicks, may raise adolescents’ vitamin D levels. Therefore, if any awareness programs or campaigns could be conducted for both parents and adolescents, it might be beneficial for reducing vitamin D deficiency.Bioresearch Commu. 10(2): 1501-1515, 2024 (July)